La suspensión de labores por caso fortuito y fuerza mayor: análisis legal y casuístico - Lora Álvarez, Germán (2016)
This article addresses the theme referred to the remedies of the suspension of work by reason of fortuitous event or force majeure. Through an analysis of the current legislation in the subject and administrative precedents, the author examines how this regulation is applied, and how this mechanism allows or not the labour continuity. By recognizing labour continuity as the foundation of the suspension of work by reason of fortuitous event and force majeure, the author concludes in the need for legal mechanisms to enable the employment relationship flexibilization.